Elective embryo or fetal reduction for caesarean scar pregnancy combined with intrauterine pregnancy - J.R. Huang; X. Li; Q.Z. Peng; J.J. Zhang; X.X. Lin; L.Q. Xie; X.H. Wu; W.S. Zhang (IMR Press, 2020)
Objective: The purpose of this study is to report and discuss the use of elective embryo reduction to treat a cesarean scar pregnancy (CSP) combined with intrauterine pregnancy after assisted reproduction, and its clinical outcomes. Material and Methods: Clinical data from six patients who were diagnosed with CSP combined with intrauterine pregnancy were retrospectively collected and analyzed. Four patients underwent elective embryo or fetal reduction following local injection of potassium chloride (reduction group), while the other two patients chose to continue their multiple pregnancies (observation group). Results: All patients were pregnant with multiple chorionic and amniotic fetuses after assisted reproduction. Mild placenta accreta was observed in one patient in the reduction group. In this group, hemorrhage volume during delivery was from 400 to 900 mL, and the average birth weight was 2,776 g. Placenta accreta spectrum occurred in both patients in the observation group, and they gave birth prematurely between 32 and 34 weeks. Conclusion: CSP combined with intrauterine pregnancy was treated using elective embryo or fetal reduction, which may improve maternal and fetal safety. Content: Outcomes of cesarean scar pregnancy with intrauterine pregnancy with or without elective embryo reduction.